2011
DOI: 10.1371/journal.pone.0020337
|View full text |Cite
|
Sign up to set email alerts
|

Asthma Pregnancy Alters Postnatal Development of Chromaffin Cells in the Rat Adrenal Medulla

Abstract: BackgroundAdrenal neuroendocrine plays an important role in asthma. The activity of the sympathoadrenal system could be altered by early life events. The effects of maternal asthma during pregnancy on the adrenal medulla of offspring remain unknown.Methodology/Principal FindingsThis study aims to explore the influence of maternal asthma during pregnancy on the development and function of adrenal medulla in offspring from postnatal day 3 (P3) to postnatal day 60 (P60). Asthmatic pregnant rats (AP), nerve growth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 33 publications
0
20
0
Order By: Relevance
“…This result suggested that asthma can affect the development of the adrenal medulla in utero [10]. Interestingly, our recent results also showed that when these offspring rats matured, their susceptibility to OVA-induced asthma was increased due to the dysfunctional adrenal medulla (unpublished data).…”
Section: Introductionmentioning
confidence: 64%
See 1 more Smart Citation
“…This result suggested that asthma can affect the development of the adrenal medulla in utero [10]. Interestingly, our recent results also showed that when these offspring rats matured, their susceptibility to OVA-induced asthma was increased due to the dysfunctional adrenal medulla (unpublished data).…”
Section: Introductionmentioning
confidence: 64%
“…Furthermore, our recent study indicated that asthma during rodent pregnancy was able to promote AMCCs to differentiate into neurons in the offspring rat pups and inhibited their ability to synthesize EPI. This result suggested that asthma can affect the development of the adrenal medulla in utero [10] . Interestingly, our recent results also showed that when these offspring rats matured, their susceptibility to OVA-induced asthma was increased due to the dysfunctional adrenal medulla (unpublished data).…”
Section: Introductionmentioning
confidence: 91%
“…Bronchoalveolar lavage fluid (BALF) was centrifuged at 1,000 rpm for 10 min at 4°C. The sediment was then stained with May-Grunwald-Giemsa and a total of 300 cells were counted (33).…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, MoTr could upregulate EPI and CORT levels. This could explain the occurrence of airway hyperresponsiveness among endurance athletes after competitions because the blunted sympathoadrenal system is unable to release sufficient EPI to dilate the bronchus (12,16,33) after prolonged high-intensity training. The time required for rats to reach exhaustion was used to evaluate the efficacy of different training regimens in inducing exercise tolerance.…”
Section: L608 Adrenal Medulla Cells Conversion In Eibmentioning
confidence: 99%
“…Moreover, maternal asthma during pregnancy has been shown to result in dysfunction of bronchial relaxation in offspring rats via inhibition of epinephrine synthesis. 47 Furthermore, maternal hypoxia has been shown to affect fetal growth, placental function, and length of gestation, [48][49][50] and these birth outcomes have been linked with adverse health outcomes in numerous studies. 51,52 Therefore, maternal hypoxia may, via restricted fetal oxygenation, result in multiple organ pathology that manifests in a wide range of offspring diseases.…”
mentioning
confidence: 99%